Estratégias de enfrentamento vivenciadas por mulheres com diagnóstico de câncer de mama em uso de tamoxifeno - Leite, Franciéle Marabotti Costa (2008)
Mammary neoplasia triggers in women a broad set of cognitive and behavioral responses that focus on developing coping strategies to deal with internal and external demands. Being a dynamic process and by demanding responses at each stage of disease, it becomes fundamental that women acquire coping abilities to confront the stressful context of the disease. The present study aimed to identify strategies used by women diagnosed with breast cancer and in use of tamoxifen and to examine the relationship between different types of coping and sociodemographic, clinical and gynecological variables. This is a descriptive, cross sectional, quantitative study carried out at Hospital Santa Rita de Cássia’s ambulatory in Vitória/ES with a sample of 270 women. Data collection used interviews registered in formularies, a scale to measure strategies of coping and an instrument to determine socioeconomic status (ABEP). Stage of disease was collect from patient’s hospital files. All data was analyzed using Statistical Package for Social Sciences (SPSS) version 13.0 (2004). Results show the strategy of coping focused on the problem as the most commonly used by women; the following variables presented statistic association (pvalue<0.0001) with the definition of the type of coping strategy used: age, education level, place of residency, family income, PREMMA, tamoxifen’s collateral effects, socioeconomic status, type of treatment and disease stage. Therefore, sociodemographic and clinical aspects can exert influence on women’s predominantly used coping strategies since they can be perceived as day to day stress factors.